(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2023)
This article explores the role of socio-community organizations in access to justice, according to the perspective of a woman who suffered gender-based violence. Although it is related to a broader project that investigates the obstacles and determinants in access to justice based on the testimony of a variety of agents, we chose to present this biographical case because of its relevance. Indeed, the extensive analysis of the complainant’s account, obtained in the context of an interview and a focus group, allows us to conclude that the rapprochement with the organization operated as a turning point in his personal trajectory and in his journey through the Justice delivery system. We argue that the organization opened for her, paraphrasing the interviewee, a “giant door” by allowing her to recognize the violence suffered as a social, political and legal problem. At the same time, it increased the effectiveness of its judicial proceedings by promoting legal know-how and registering the request for justice and reparation for the rights infringed in the public sphere.